Computed Tomography Scan Correlation of Position of Appendix with Present Literature - Kachare, Manohar; Patil, Abhijit D.; Gamanagatti, Shanta A.; Kulkarni, Sanjay B. (Journal of Gastrointestinal and Abdominal Radiology, 2024)
Background The appendix exhibits varied anatomical orientations, which significantly influence the diagnosis and treatment of appendicitis. Existing literature predominantly relies on cadaveric studies to delineate common appendix positions, lacking comprehensive computed tomography (CT)-based investigations on a large scale. Thus, our study endeavors to delineate the prevailing position of the appendix on CT scans and ascertain its concordance with existing literature, thereby augmenting our understanding of this anatomical entity. This cross-sectional study was conducted in a tertiary care hospital setting.Materials and Methods A total of 1,068 patients aged 18 years and older, undergoing abdominal CT scans at the hospital between July 2020 and July 2021, were enrolled in the study, with exclusion criteria applied to conditions that could distort anatomical features. The position of the appendix was meticulously documented for each patient, alongside measurements including diameter, wall thickness, and origin. Data collection utilized a predefined Microsoft Excel sheet. Subsequently, numerical and relative frequencies were computed for appendiceal positions and origins. Additionally, diameter and wall thickness were assessed, and pertinent parameters were derived.Results The relative frequencies of various potential appendiceal positions observed in our study were as follows: subcecal: 6.6%; paracecal: 1.2%; pelvic: 21.9%; postileal: 32.9%; preileal: 6.7%; retrocecal: 28.5%; subhepatic: 2.2%.Conclusion In contrast to traditional assumptions, our findings reveal that the most prevalent positions of the appendix are postileal, retrocecal, and pelvic, challenging historical beliefs.
Keywords: appendix; positions; MDCT; in vivo